Smart letter box / Abdul Wafi Abd Majid & Muhammad Nurhaiqal Ahmad Kamal - Abd Majid, Abdul Wafi; Ahmad Kamal, Muhammad Nurhaiqal (2015)
Nowadays, people communicate every day. People speak, write and draw to let others know what they thinking and feelings. When those people respond, the communication become interactive or two-way. We make decision to build a project Smart Letterbox. The main objective of this project to study requirement and procedure needed for Smart Letterbox, to develop mechanical and electronic part in order to improve the current letterbox system, and lastly to study and utilize the necessary component to fabricate the project. It is about combination of hardware part and programming part with Liquid crystal display(LCD), and buzzer using Programmable Interface controller(PIC). The sensor be able to notice the present of letter through LCD and buzzer. For this project, we make circuit for the sensor to detect the letter. Then, interface it with PIC. MP LAB X software include for this project to program the PIC and proteus to run the whole project. Expected result is to make sure the LCD is used to display the information and buzzer to alert the user. In a nutshell, this Smart Letterbox can ease and help people receive the information smoothly.